PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA GURU PADA SMA NEGERI 4 TORAJA UTARA - Gelianti, Gelianti; Pongtuluran, Althon K.; Pundissing, Rati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The Influence of Leadership Style and Work Discipline on Teacher Performance at SMA Negeri 4 North Toraja. The aim of this research is to analyze the influence of leadership style and work discipline on teacher performance at SMA Negeri 4 North Toraja. The data collection procedures for this research are: observation, interviews and questionnaires. The data analysis technique is quantitative with multiple linear regression tests. The research results show (1) the Leadership Style variable (X1) partially has a significant effect on Teacher Performance (Y) at SMA Negeri 4 North Toraja. This is shown by the obtained value of tcount 1.825 > ttable 1.676. (2) Work Discipline (X2) partially has a significant effect on Teacher Performance (Y) at SMA Negeri 4 North Toraja. This is shown by the obtained value of tcount 1.710 > ttable 1.673. (3) Simultaneously Leadership Style (X1) and Work Discipline (X2) influence Teacher Performance at SMA Negeri 4 North Toraja. This is shown by the obtained value of Fcount12,692>Ftable3,197.